Leopoldo Franchetti in Abruzzi and Molise (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
This introductory note takes into consideration some aspects and moments of Leopoldo Franchetti’s life, which are little considered. The pivotal moments examined are: the influence of the cultural experience of positivism on Franchetti’s education; Franchetti’s studies at the University of Pisa; conservative reformism and the discovery of Italy ‘Southern question’; foreign travels to Germany, England and France; expeditions to Abruzzo and Molise; the meeting with Pasquale Villari.
Keywords: Leopoldo Franchetti; Positivism; Conservative Reformism; Southern Question; Pasquale Villari